2004
DOI: 10.1007/s00418-004-0662-4
|View full text |Cite
|
Sign up to set email alerts
|

A new rat type I-like alveolar epithelial cell line R3/1: bleomycin effects on caveolin expression

Abstract: The study of function and regulation of the phenotype of alveolar type I (AT I) epithelial cells is limited by the rareness of suitable cell lines or primary cultures of this cell type. We describe in the present study the type I-like rat epithelial cell line R3/1. This cell line displays in vitro a phenotype with several characteristic features of AT I cells. R3/1 cells were analysed for mRNA and protein content of markers related to the AT I cell type (T1alpha, ICAM-1, connexin-43, caveolins-1 and -2) and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 52 publications
(51 reference statements)
2
43
0
Order By: Relevance
“…Both cell lines have properties similar to those of AEC I (Kathuria et al, 2007;Koslowski et al, 2004). We confirmed that E10 cells had a very high expression of P2X 7 R and that R3/1 cells expressed little P2X 7 R (Fig.…”
Section: Bzatp Stimulates Surfactant Secretion In a Heterocellular Cusupporting
confidence: 77%
See 1 more Smart Citation
“…Both cell lines have properties similar to those of AEC I (Kathuria et al, 2007;Koslowski et al, 2004). We confirmed that E10 cells had a very high expression of P2X 7 R and that R3/1 cells expressed little P2X 7 R (Fig.…”
Section: Bzatp Stimulates Surfactant Secretion In a Heterocellular Cusupporting
confidence: 77%
“…Another line of evidence favoring P2X 7 R as a mediator for the increase in surfactant secretion comes from co-culture of P2X 7 Rexpressing cells with AEC II. Two lung cell lines, E10 and R3/1, have AEC-I-like properties (Kathuria et al, 2007;Koslowski et al, 2004). However, E10 cells express a high level of P2X 7 R, whereas R3/1 cells have little P2X 7 R (Barth et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As confirmed by immunofluorescence analysis (Fig. I), R3/1 cells have been characterized as an adequate model to study in vitro AT-I cells and express RAGE and RTI40/TI-alpha, two well-characterized markers for AT-I cells, on cell surface (16,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 72%
“…12 Nonetheless, although Cav-2 is highly expressed in the lungs, investigation of its role in lung fibrosis is still neglected.…”
Section: Report Reportmentioning
confidence: 99%